Development of the Academic Supervision Model Based on Differentiated Learning in Inclusive Schools - Priyanti Rusanti S; Murtadhlo Murtadhlo; Budiyanto Budiyanto; Nunuk Hariyati; Hitta Alfi Muhimmah; Ts. Syariffanor binti Hisham (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to develop an academic supervision model based on differentiated learning, evaluate its feasibility, and measure its effectiveness. Method: The research employs the ADDIE model development methodology. Data were collected through interviews, observations, and questionnaires in two inclusive senior high schools in Sidoarjo. Results: The findings indicate that (1) The academic supervision model based on differentiated learning includes stages that incorporate elements of differentiated learning into every supervision instrument. These elements cover the assessment preparation to evaluate student's readiness, interest, learning profiles, and the implementation of teaching processes, including content, process, and learning outcomes. (2) The academic supervision model based on differentiated learning is deemed feasible. The score obtained from subject matter experts indicates that the developed instruments and guidebooks meet the criteria for "very feasible." (3) Based on the results of the normalized gain test, the mean difference between the pre-test and post-test indicates that the developed product has a high level of effectiveness and is suitable for use as an academic supervision instrument. Novelty: This research emphasized the development of an academic supervision model based on differentiated learning in inclusive schools.